AB0659 SECUKINUMAB PROVIDES SIGNIFICANT IMPROVEMENT OF SPINAL PAIN IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS: RESULTS FROM THE 24-WEEK PHASE 3 SKIPPAIN STUDY. (2nd June 2020) - Poddubnyy, D.; Pournara, E.; Zielińska, A.; Baranauskaite, A.; Muñoz Jimenez., A.; Kumari, P.; Schulz, B.; Rissler, M.; Perella, C.; Marzo-Ortega, H.
Abstract : Background: Spinal inflammation causing back pain is a hallmark of axial spondyloarthritis (axSpA) mainly affecting the sacroiliac joints and spine. 1 Spinal pain is the most burdensome symptom resulting in substantial functional limitations and impairment of health-related quality of life. Objectives: SKIPPAIN (NCT03136861 ) evaluated efficacy and safety of secukinumab (SEC) in reducing spinal pain in patients (pts) with axSpA who had an inadequate response to NSAIDs. Methods: SKIPPAIN, a 24 week (wk), randomised, double-blind, multicentre trial, enrolled axSpA pts (aged ≥18 years) with active disease defined by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score ≥4 and average spinal pain numerical rating scale (NRS) score >4 at baseline (BL) and inadequate response to ≥2 NSAIDs ≥4 wks. The trial had a PBO-controlled period from BL to Wk 8 and a SEC 150/300 mg period from Wk 8 to Wk 24. Primary and key secondary endpoints were superiority of SEC 150 mg compared to PBO in achieving average spinal pain score <4 on a 0–10 NRS and BASDAI score <4 at Wk 8, respectively. Results: 380 axSpA pts (269 (70.8%) AS and 111 (29.2%) nr-axSpA) were randomised to SEC 150 mg (N=285) or PBO (N=95). Demographic and BL characteristics are presented in Table 1 . Proportion of responders, in terms of average spinal pain, was 31.9% vs. 20.0% for SEC vs PBO (p<0.05) and proportion of pts with BASDAI score of <4 was 33.3% vs. 23.2% for SEC vs PBO (p<0.05), respectively at Wk 8 (Table 2 ). After Wk 8, responder rates increased with SEC treatment. No unexpected safety events were reported. Conclusion: Secukinumab provided significant improvement of spinal pain in pts with axSpA. SEC was well tolerated with a safety profile consistent with previous reports. 2 References: [1]Danve A & Deodhar A. Clin Rheumatol . 2019;38:625-34. [2]Deodhar A, et al. Arthritis Res Ther . 2019;21(1):111. Disclosure of Interests: Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Effie Pournara Shareholder of: Novartis, Employee of: Novartis, Agnieszka Zielińska Consultant of: Novartis, Pfizer, Asta Baranauskaite Consultant of: AbbVie, Speakers bureau: Novartis, AbbVie, Amgen, Roche, KRKA, Alejandro Muñoz Jimenez.: None declared, Preeti Kumari Employee of: Novartis Healthcare Pvt. Ltd., Barbara Schulz Employee of: Novartis, Michael Rissler Shareholder of: Novartis, Employee of: Novartis, Chiara Perella Shareholder of: Novartis, Employee of: Novartis, Helena Marzo-Ortega Grant/research support from: Janssen, Novartis, Consultant of: Abbvie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, Takeda, UCB